A Case of Recurrent Esophageal Cancer Treated with Concurrent Chemoradiation Therapy in Pregnancy - Kaori Yamada; Yoshitsugu Chigusa; Motoo Nomura; Katsuyuki Sakanaka; Mitsuhiro Nakamura; Shinsuke Yano; Shigeru Tsunoda; Eiji Kondoh; Masaki Mandai (Hindawi Limited, 2018)
Esophageal cancer rarely coincides with pregnancy, and only five cases have been reported thus far. The management of esophageal cancer during pregnancy is extremely challenging due to its aggressive nature. We herein report a case of recurrent esophageal cancer in pregnancy. A 41-year-old multigravida with a history of esophageal squamous cell cancer treated with esophagectomy and perioperative chemotherapy was diagnosed with local recurrent carcinoma of the residual esophagus at 16 weeks of gestation. The patient strongly desired to continue the pregnancy, and concurrent chemoradiation therapy (CRT) consisting of 50.4 Gy of radiation, cisplatin, and 5-fluorouracil was carried out from 19 weeks of gestation. CRT was dramatically effective, and the recurrent lesion disappeared. At 38 weeks of gestation, she underwent cesarean section and delivered a healthy female baby. Both maternal and fetal courses were satisfactory, and the patient has been free of disease for 12 months. This is the first case of recurrent esophageal cancer in pregnancy in which CRT was completed without reducing treatment intensity and led to a complete response. Nevertheless, little is known regarding the safety and possible adverse effects of CRT on the fetus. Therefore, deliberate selection of patients and long-term follow-up of the child are necessary.